Beyond subordination vs. resistance: An intersectional approach to the agency of veiled muslim women - Bilge, Sirma (Journal of Intercultural Studies, 2010)
Engaging with a figure that came to operate as a powerful cultural signifier of otherness in debates over migrant/Muslim integration across the West, the ‘veiled woman’; the paper questions the idea of agency that inheres in the contemporary feminist discourses on Muslim veil. After showing the shortcomings and adverse effects of two dominant readings of the Muslim veil, as a symbol of women's subordination to men, or as an act of resistance to Western hegemony, it explores an alternative avenue drawing on both the poststructuralist critique of the humanist subject and feminist intersectional theorising to answer the question of what kind of conception of agency can help us to think about the agency of the veiled woman without binding a priori the meaning of her veiling to the teleology of emancipation, whether feminist or anti-imperialist.
Keywords: agentivité; approches et analyses; discipline; discours dominant; droits des femmes*; femmes* musulmanes; intersectionnalité; post-structuralisme; ressource en ligne; sciences humaines; sociologie; systèmes d'oppression; thématiques; voiles islamiques